KINERJA PEGAWAI DAN FAKTOR YANG MEMPENGARUHINYA: Studi Kasus di STAIN Pekalongan - Zaenal Mustakim (JURNAL PENELITIAN, 2014)
The success of an institution is influenced by the level of employee performance. This study revealed two main issues, namely (1) STAIN Pekalongan employee performance based on tenure, age, and sex; (2) the factors that influence employee performance. The results of this study reveal that: First, based on tenure, employee with tenure over 10 years are on average performance (mean score is 3.95 or 79%); tenure ≥ 5 <10 years are also on average performance (mean score is 4.00 or 80%); and tenure <5 years are on high performance (mean score is 4.04 or 81%). Based on age, employees over 35 years old are on average performance (mean score is 3.96 or 79.2%); under 35 years old are on high performance (mean score is 4.03 or 81%). Based on sex, male employee are on high performance (mean score is 4.06 or 81.22%), female employees are on average performance (mean score is only 3.95 or 79.08%). Second, the factors that influence employee performance are the state of the workspace clean and neat; job training; application of finger print; salary increases; reward on job performance; and changes in leadership.